Associations between body mass index, physical activity, and motor competence in children aged 3–12 years: a systematic literature review - Eni Rispayanti; Tjung Hauw Sin; Wilda Welis; Anton Komaini; Sri Gusti Handayani (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
This systematic literature review was designed to synthesize the latest research on the associations among BMI, physical activity and motor competence in children aged 3–12 years and to present the methodological map of this field. Following the PRISMA 2020 format, this review undertook a structured Scopus database search of publications from 2020 to 2026 (search conducted on 30 June 2026). Upon elimination of non-English and document-type-ineligible records (43), a total of 520 records were screened by title and abstract. Of these, 120 reports were retrieved and 111 were full-text assessed. Fifty studies were finally included in the synthesis after application of the predefined eligibility and quality (FICO) criteria. Four thematic findings were revealed. To begin with, the link between higher BMI and poorer motor competence was not only consistent, but could also be traced down to very early childhood years. Secondly, physical activity and motor competence were mutually beneficial and positively related, quite often their relationship was indirect and going through physical fitness. Thirdly, both motor-skill and multicomponent interventions brought about improvements in motor competence as well as adiposity-related outcomes, especially in children with problems of overweight or obesity. Fourthly, motor competence correlates existed on the level of individual, family and environment. Conceptually the results push forward reciprocal and developmental frameworks of motor competence; on the other hand, they give support to the idea of early, skill-centered physical-activity promotion in educational and community settings. Further studies would do well to focus on longitudinal, compositional, and intervention designs that regulate the use of motor-assessment tools in an effort to identify causal relationships and help the formulation of policies that can be implemented on a large scale.